Discussion of Disclosure of Estimates of Holding Gains and the Assessment of Systematic Risk - Boatsman, James R.; Revsine, Lawrence (Journal of Accounting Research, 1978)
James R. Boatsman, Lawrence Revsine, Discussion of Disclosure of Estimates of Holding Gains and the Assessment of Systematic Risk, Journal of Accounting Research, Vol. 16, Studies on Changes in General and Specific Prices: Empirical Research and Public Policy Issues (1978), pp. 96-105